Effects of Visible Spectrum on Potential Differential Response to Soybean Sprouts (Glycine max (L.) Merill) during photosynthesis - Farida Wahyuni; Unggul P. Juswono; Kusharto Kusharto (Natural B, Journal of Health and Environmental Sciences, 2012)
The absorption visible light spectrum by chlorophyll cause excited electron. The transition of electron in photosynthesis process result electrical potential difference response which can be utilized to spur metabolism process in the plants itself. This research used the seedling of Glycine max (L.) and the varietas is sindoro. The measurement of the potential difference response is done by adding of visible light (red, yellow, green, blue and violet) alternately to the bean sprouts of Glycine max (L.) Merill. The light distribution is being done for 1 second, 5 second and constantly. The result of the research showed the effect of the visible light distribution constantly in the photosynthesis process. In the red light occurs maximum potential difference response. In peak I resulted -147,3 mV and peak II resulted -137 mV. The minimum potential difference response is resulted by green light. in peak I resulted -68,8 mV and peak II resulted -56,75 mV. The effect of the visible light distribution during any time in the photosynthesis process. In the red light occurs maximum potential difference response. In peak I resulted -119,2 mV for 1 second and -146 Mv for 5 second. In peak II resulted - 112,3 mV for 1 second and -125,5 mV for 5 second. The minimum potential difference response is resulted by green light. In peak I resulted -64,75 mV for 1 second, -69,5 mV for 5 second, and in peak II resulted -55,9 mV for 1 second and -56 mV for 5 second.